2020
DOI: 10.1111/odi.13684
|View full text |Cite
|
Sign up to set email alerts
|

Functional study of novel PAX9 variants: The paired domain and non‐syndromic oligodontia

Abstract: Objectives To investigate pathogenic variants of the paired box 9 (PAX9) gene in patients with non‐syndromic oligodontia, and the functional impact of these variants. Subjects and Methods Whole exome sequencing and Sanger sequencing were utilized to detect gene variants in a cohort of 80 patients diagnosed with non‐syndromic oligodontia. Bioinformatic and conformational analyses, fluorescence microscopy and luciferase reporter assay were employed to explore the functional impact. Results We identified three no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 35 publications
7
23
0
Order By: Relevance
“…Microdontia or peg-shaped lateral incisors were observed in 6/10 cases (60%) (II:4 was excluded due to uncertain microdontia phenotype). These findings are consistent with previous studies, reviews, and meta-analyses demonstrating that the heterozygous PAX9 variants are associated with certain tooth agenesis phenotypes, including (1) oligodontia, (2) nonsyndromic, (3) molar dominated, and (4) microdontia or peg-shaped lateral incisors [11,15,16,31,32]. Consistently, a review paper by Fournier et al (2018) showed that the absence of upper and lower third molars was observed in 95% and 90% of the patients with PAX9 variants, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Microdontia or peg-shaped lateral incisors were observed in 6/10 cases (60%) (II:4 was excluded due to uncertain microdontia phenotype). These findings are consistent with previous studies, reviews, and meta-analyses demonstrating that the heterozygous PAX9 variants are associated with certain tooth agenesis phenotypes, including (1) oligodontia, (2) nonsyndromic, (3) molar dominated, and (4) microdontia or peg-shaped lateral incisors [11,15,16,31,32]. Consistently, a review paper by Fournier et al (2018) showed that the absence of upper and lower third molars was observed in 95% and 90% of the patients with PAX9 variants, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…We identified that the p.Arg77Gln did not compromise the intracellular localization of PAX9, but significantly reduced the transactivation of BMP4, the downstream target of PAX9. Recently, the PAX9 variant c.229C > G (p.Arg77Gly), adjacent to the c.230G > A, was reported in a patient who had 17 missing teeth (four third molars, four second molars, two first molars, three premolars, one canine, and two maxillary lateral incisors) [11]. The p.Arg77Gly reduced BMP4 transactivation and localized in the nucleus, similar to the p.Arg77Gln.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…To date, a number of genes have been found to be associated with non-syndromic tooth agenesis, including axin inhibition protein 2 ( AXIN2 ), muscle segment homeobox 1 ( MSX1 ), paired box 9 ( PAX9 ), ectodysplasin A ( EDA ), wingless-type mouse mammary tumor virus integration site family member 10A ( WNT10A ), wingless-type mouse mammary tumor virus integration site family member 10B, low-density lipoprotein receptor-related protein 6 ( LRP6 ), and opsin 3 ( OPN3 ) [ 2 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. As one of the earliest discovered pathogenic genes of tooth agenesis, PAX9 has been a research hotspot [ 2 ].…”
Section: Introductionmentioning
confidence: 99%